HUBUNGAN KESEJAHTERAAN SPIRITUAL DENGAN KUALITAS TIDUR PADA PASIEN HIV/AIDS DI RSUD SULTAN IMANUDDIN PANGKALAN BUN - Martina Sindi Florika; Zuliya Indah Fatmawati; Eko Budi Laksono; Ade Sucipto (Journal Integrative and Holistic Health Studies, 2025)
HIV is a virus that attacks the human immune system and weakens the body's defenses against various diseases. This virus infects white blood cells and weakens the immune system, making infected individuals susceptible to various opportunistic infections. If left untreated, this infection can lead to AIDS (Acquired Immune Deficiency Syndrome), a series of symptoms resulting from the weakened immune system caused by the HIV virus. This study investigated the relationship between spiritual well-being and sleep quality in HIV/AIDS patients. This study used a descriptive analysis design with a sample of 58 respondents. Sampling was conducted using purposive sampling. Data were collected using the Functional Assessment of Chronic Illness Therapy-Spiritual Well-Being (FACIT-SP12) and the Pittsburgh Sleep Quality Index (PSQI). Univariate data analysis was performed using frequency distributions, and bivariate data analysis was performed using descriptive analysis. All respondents reported high levels of spiritual well-being. Most reported good sleep, while nearly half reported poor sleep. Descriptive analysis revealed a relationship between spiritual well-being and sleep quality. Descriptive analysis indicated that higher levels of spiritual well-being resulted in better sleep quality. This study demonstrates a relationship between high levels of spiritual well-being and sleep quality in HIV/AIDS patients.